2021
DOI: 10.3390/axioms10040283
|View full text |Cite
|
Sign up to set email alerts
|

Some New Post-Quantum Integral Inequalities Involving Twice (p, q)-Differentiable ψ-Preinvex Functions and Applications

Abstract: The main motivation of this article is derive a new post-quantum integral identity using twice (p, q)-differentiable functions. Using the identity as an auxiliary result, we will obtain some new variants of Hermite–Hadamard’s inequality essentially via the class of ψ-preinvex functions. To support our results, we offer some applications to a special means of positive real numbers and twice (p, q)-differentiable functions that are in absolute value bounded as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In [41], Kunt et al found some (q 1 , q 2 ) analogues of H-H-type inequalities and midpoints. Cortez et al obtained the integral identities via the φ preinvex function in [42]. Using new ideas [41,43], in recent years, numerous authors have provided other refinements and extensions of the inequalities [44][45][46] of the H-H and Ostrowski types [18,38,44,[47][48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…In [41], Kunt et al found some (q 1 , q 2 ) analogues of H-H-type inequalities and midpoints. Cortez et al obtained the integral identities via the φ preinvex function in [42]. Using new ideas [41,43], in recent years, numerous authors have provided other refinements and extensions of the inequalities [44][45][46] of the H-H and Ostrowski types [18,38,44,[47][48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the concept of the (p, q) b -integral and (p, q) bderivative over finite intervals was proposed by Vivas-Cortez et al [29] in 2021. In the past few years, the topic of (p, q)-calculus has become interesting in various integral inequalities for many researchers, and the results of (p, q)-calculus can be found in [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45], and the references cited therein.…”
Section: Introductionmentioning
confidence: 99%